Analisis penerapan pajak restoran pada penjualan (Studi kasus Rumah Makan Geprek Jo Manado) - Maramis, Dennis Piere; Ilat, Ventje; Mawikere, Lidia (Indonesia Accounting Journal, 2020)
The tax is a compulsory contribution of citizens to the government and is imposed on the public based on the provisions of applicable law. Consideration of the cost of goods sold for a product and how to calculate restaurant taxes is one of the crucial things in a restaurant business, in an era where UMKM Â have been increasingly prioritized by the government to build a stronger national economy, pricing and tax calculation for a product is very important by the business of the people or companies. One type of tax whose potential is growing along with the increase in the leisure or tourism business is restaurant tax. This study aims to determine the application of restaurant taxes on the main cost of selling at geprek jo restaurant. The analytical method used in this thesis research is a qualitative descriptive method. Geprek Jo restaurant is a restaurant with a mainstay menu of Chicken and Tuna in Geprek with special chili seasonings Geprek Jo restaurant which was established in September 2018. Calculation of cost of goods sold consists of raw material costs, direct labor costs and costs restaurant overhead, and calculate initial inventory, ending inventory, purchases and production in progress. The results of the calculation of cost of goods sold which require inventory elements get a smaller figure than the selling price of the product after classification. Then there are still benefits for the company. The results obtained that the cost of goods sold at Jo Geprek Restaurant is influenced by restaurant taxes.